Studies on the nutrition of grazing ruminants : collected papers : thesis submitted to Massey University, New Zealand for the degree of Doctor of Science - Corbett, John Lovick (Massey University, 1967)
The majority of the world's cattle and sheep obtain most of their feed by grazing, yet studies on housed ruminants and experiments on the growth of grassland herbage that exclude grazing animals outnumber direct investigations of animal production from pasture. Such studies are a legitimate approach towards, and make necessary contributions to, an understanding of the processes involved in pastoral systems, but in themselves they are not sufficient to gain a full appreciation of these processes which entail complex interactions between climate, soil, plant and animal.
This thesis is a Doctor of Science and as such comprises many published works. Copyright restricts their inclusion. The list of submitted publications can be found in the PDF files below and the full text found in journals themselves.
Keywords: Grazing; Rumination; Ruminants; Nutrition